Status of low-energy accelerator-based BNCT worldwide and in Argentina. (December 2020) - Cartelli, D.E.; Capoulat, M.E.; Baldo, M.; Sandín, J.C. Suárez; Igarzabal, M.; Grosso, M.F. del; Valda, A.A.; Canepa, N.; Gun, M.; Minsky, D.M.; Conti, G.; Erhardt, J.; et al.
Abstract: Existing and active low-energy Accelerator-Based BNCT programs worldwide will be reviewed and compared. In particular, the program in Argentina will be discussed which consists of the development of an Electro-Static-Quadrupole (ESQ) Accelerator-Based treatment facility. The facility is conceived to operate with the deuteron-induced reactions 9 Be(d, n) 10 B and 13 C(d, n) 14 N at 1.45 MeV deuteron energy, as neutron sources. Neutron production target development status is specified. The present status of the construction of the new accelerator development laboratory and future BNCT centre is shown. Highlights: The current status of low-energy projects and associated facilities for AB-BNCT worldwide are reviewed. The recent progress of the Argentine AB-BNCT program is described. Deuteron induced reactions 9 Be(d, n) 10 B and 13 C(d, n) 14 N at 1.45 MeV deuteron energy as neutron sources. Machine development status is described. Neutron production target development status is specified.